Fire Properties of Intumescent Coating Systems for the Rolling Stock - Norbert Radek; Renata Dwornicka (Communications - Scientific letters of the University of Zilina, 2020)
This paper presents results of the experimental research aimed at fire and smoke properties of rolling stock coating system. The overriding research task was to meet current European requirements in the field of fire properties with maintaining the desired performance parameters, such as protective and decorative properties. The research determined parameters such as flame spreading over the surface and heat emission of coating system prepared on steel substrate. Research was carried out to find the optimum thickness of intumescent layer. The tests have shown the effectiveness of use of a protective paint that allows meeting the requirements in the field of fire safety.